The effect of materials and obliquity of the impact on the critical velocity of rebound. Issue 3 (4th March 2017) - Kuuluvainen, Heino; Arffman, Anssi; Järvinen, Anssi; Harra, Juha; Keskinen, Jorma
ABSTRACT: The critical velocity of rebound was determined for spherical ammonium fluorescein particles in the size range of 0.44–7.3 μm. The method was based on measurements with a variable nozzle area impactor (VNAI) and numerical simulations. A comparison to previous results with spherical silver particles obtained with the same method showed that the critical velocity was approximately two orders of magnitude higher for ammonium fluorescein than for silver at the same size range. Among the hard test materials, including steel, aluminium, molybdenum, and Tedlar, the surface material had no significant effect on the critical velocity of rebound within the accuracy of the method. On the contrary, the critical velocity was observed to be highly dependent on the obliquity of the impact at the onset of rebound. While the ratio of the maximum tangential and normal velocities was defined as a measure for the obliquity, the critical velocity was found to be more than a magnitude smaller for very oblique impacts with the velocity ratio above 9 than for close-to-normal impacts with the velocity ratio below 1.5. The results of this study can be considered as a link between the recently published critical velocity results for nanoparticles and the older results for micron-sized particles. Copyright © 2017 American Association for Aerosol Research